Nepalese management education at crossroads: Prospects and constraints - Katuwal, Shyam Bahadur (Bodhi: An Interdisciplinary Journal, 2013)
Bodhi: An Interdisciplinary Journal, 5, 2011, Page 144-159 DOI: http://dx.doi.org/10.3126/bodhi.v5i1.8050